KAJIAN DINAMIK EVAPORATOR SISTEM PENDINGIN PROPAN KILANG LNG STUDI KASUS: KILANG LNG - Kurniawan Sabirin, Iwan
Propane Refrigerant system with three steps pressure in LNG Plant XYZ is very important in the pre-cooling process of feed gas and Multi Refrigerant (MR) to temperature -38?C. The problem with this system will affected to LNG production. The problem has been existed since 1999 in the Propane system. The liquid level of Propane is frequently lost in the medium pressure Evaporator to cool down feed gas even expansion valve that control the level had fully open. It also made the liquid level problem in the low pressure Evaporator since the liquid is coming from the medium pressure Evaporator. Several efforts had been made like checking inside of the line and expansion valve from plugging, increase Cv of valve, and increase pipe diameter from separator (flash drum) to Evaporator. These effort did not solve the problem very well since there is still problem with slow response to the immediate change in the LNG production. It will took 9,5 hours longer than normal 2,5 hours to increase the LNG production about 120 m3/hr and keep the liquid Propane level stable at setpoint. Process simulation using process simulator software like HysysTM to make dynamic modeling system of Propane refrigerant system will help to analyze and solve the problem. The result of this study is plugging in the pipe or expansion valve of MP Evaporator to the equal of Cv 250 USGPM showed the similar condition of the problem that leads to biggest probability of the root cause. Recommendation of this study is to install flow meter for Propan liquid and vapor at the each of Evaporator input and output to have ability to calculate mass balance and define exact problem and location. vii Utilizing pressure control at Propane Accumulator will maintain constan pressure in the system and improve Evaporator duty and lower Feed Gas temperature at the outlet of Evaporator. But Propane in the vapor phase send out from the system quite big. It needs to utilize as fuel gas for boilers or reconditon back to liquid for make-up to the system. More similar process model of kettle Evaporator with liquid level control will give more accurate result.